2009
DOI: 10.1007/s00421-009-0996-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aquatic resistance training on health and fitness in postmenopausal women

Abstract: To investigate effects of 24 weeks of resistance training with aquatic resistance devices or elastic bands (EB) on markers of cardiovascular health and physical capacity. Forty-six healthy, sedentary postmenopausal women participated. The groups were aquatic exercise (AE; n = 15), EB (n = 21), and control (n = 10). Venous blood chemistry included cholesterol, triglycerides, glucose, and apolipoprotein B. Physical capacity was assessed by the sit-and-reach, knee push-up, 60-s squat, and abdominal crunch tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
3
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 36 publications
7
112
3
13
Order By: Relevance
“…Earlier studies reported that there was an improvement in ADL as lower extremity and trunk muscle strength were augmented by aquatic exercise training (Colado, et al, 2009). Katsura et al (2010) reported that lower extremity strength increased as a result of performing aquatic exercise training using water resistance equipment, and that the improvement in dynamic balance function was linked to alleviating fatigue in everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies reported that there was an improvement in ADL as lower extremity and trunk muscle strength were augmented by aquatic exercise training (Colado, et al, 2009). Katsura et al (2010) reported that lower extremity strength increased as a result of performing aquatic exercise training using water resistance equipment, and that the improvement in dynamic balance function was linked to alleviating fatigue in everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that the strength of lower extremity, trunk muscle and dynamic balance function for prevention of accidental falls were improved by using water-resistance-equipment (Colado, et al, 2009;Katsura, et al, 2010). As previously noted, many studies of aquatic exercise have reported its eŠects on muscle strength and balance function in elderly women.…”
Section: Introductionmentioning
confidence: 94%
“…According to Andersen et al 3 few studies have analyzed physiological adaptations induced by exercises with elastic resistance compared to other contraction modalities. Moreover, previous studies found that elastic resistance used in an adequate intensity provides significant improvements in functional tests and changes the body composition -reduction of abdominal perimetry and body fat percentage 4,5 . Surface electromyography (SEMG) allows the researcher to analyze the lower and upper limbs muscular actions during exercises.…”
Section: Introductionmentioning
confidence: 98%
“…As a physical activity, swimming can improve health, physical fi tness and the quality of life (Saavedra et al 2007, Colado et al 2009, Fletcher et al 1996, Cox et al 2008, Nualnim et al 2012. A swimming training activates all body muscles, improves the function of each system, including the muscle and cardiovascular endurance (Ferretti, et all.…”
Section: Introductionmentioning
confidence: 99%